Analysis of the probability of crisis events as a determinant of the financial security of food industry enterprises - Zhukevych, Svitlana; Zhuk, Natalia (Herald of Economics, 2023)
Introduction. In today’s conditions, financial and economic activity is affected by a number of external and internal factors that lead to the emergence of crisis phenomena, respectively, affect the level of financial security and lead to the bankruptcy of the enterprise. Such circumstances actualize the issue of predicting, preventing and countering crisis phenomena and substantiate the need to implement anti-crisis management into practical activities, the methods and models of which make it possible to assess and analyze the probability of bankruptcy and take measures to prevent it and ensure financial security.Therefore, there is a need for early determination and analysis of the probability of bankruptcy of the enterprise and diagnosis of the causes that lead to its occurrence and the possibilities of prevention in order to ensure the financial security of agents of economic activity.The goal is to study the main approaches, methods and models for analyzing the probability of the occurrence of crisis phenomena that lead to bankruptcy and affect the level of financial security of food industry enterprises.Methods. Achieving the goal is possible when using general scientific, special, economic-mathematical methods and integral discriminant models of knowledge of the investigated processes and phenomena. Comparison, generalization, analysis, synthesis, systematization are used to understand crisis phenomena, bankruptcy, financial security. Structural-logical, tabular, graphic methods, economic-statistical, discriminant models are used to determine the probability of the occurrence of crisis phenomena in the financial security system of the enterprise.Results. In the course of the research, the understanding of the crisis as an unpredictable situation, which is a threat to the priority goals of the enterprise and its financial security, was clarified. In turn, crisis phenomena lead to the inability of a business entity to fulfill its financial obligations to ensure current production activities, that is, to a financial crisis, identified with insolvency, lack of profit and potential for effective functioning, that is, with bankruptcy.It was investigated that it is possible to determine the probability of bankruptcy using methods of financial analysis - horizontal, vertical, absolute differences, structural. In addition, the complication of the conditions of financial and economic activity requires the use of static models based on discriminant analysis, which involves the assessment of the ratio of financial coefficients when constructing a function using mathematical and statistical procedures and the calculation of the integral index Z.In order to identify, analyze and assess the occurrence of crisis phenomena that threaten financial security, the most common economic and mathematical methods of predicting the probability of bankruptcy of discriminant analysis are applied. An express analysis of the financial condition of the food industry of Zhytomyr Lasoshchi CJSC was carried out using the U. Beaver coefficient. E. Altman’s model was used to determine the probability of bankruptcy of the investigated enterprise: the adapted Z-score formula (Altman Z-score Plus) for manufacturing companies, a model for private enterprises that do not place shares on the stock market, a two-factor model. The model of K. Springate, R. Lees was also used to assess the onset of crisis phenomena.However, taking into account the advantages of the applied models (they reflect various aspects of the enterprise’s economic activity, are easy to calculate, simple and accurate in calculations, give the possibility of their application to external users), they are developed for Western countries with a developed market system and do not take into account the modern conditions of domestic market management. Therefore, along with foreign models, we tested domestic models for determining the probability of bankruptcy by such economists as O. Tereshchenko and A. Matviychuk.The application and calculation of indicators of discriminant models of analysis and assessment of crisis phenomena made it possible to identify the enterprise of the food industry - CJSC «Zhytomyrski lasoshchi» and draw appropriate conclusions. However, in order to determine the specific factors influencing the probability of bankruptcy and their quantitative measurement, it is necessary to carry out a more detailed analysis for each component of the company’s financial condition.Discussion. Management of financial and economic activities of food industry enterprises requires systemic changes, qualitatively new approaches to identifying crisis phenomena at the earliest possible time of their manifestation. Since, crisis phenomena are equated with the onset of bankruptcy of an enterprise with a high degree of risk in financial activity, the result of which is the impossibility of fulfilling obligations and demands to the budget and creditors within the specified time. It is important to detect signs of a crisis in an enterprise in advance, which is possible by performing an analysis using diagnostic research methods that make it possible to determine the probability of bankruptcy with a certain accuracy and predictability. We are talking about the importance and necessity of implementing effective anti-crisis, security-oriented management in order to anticipate, prevent the occurrence of threats and take measures to correct the situation in order to achieve a high level of financial security of the enterprise in the harsh, unpredictable conditions of the market economy.Prospects for further research. In order to carry out the analysis and assessment of crisis phenomena and the probability of bankruptcy in the context of their impact on the financial security of food industry enterprises, in addition to the proposed ones, it is advisable to use other discriminating economic and mathematical methods of clear and unclear methods and models for determining crisis phenomena, which would take into account industry specifics and be adapted in conditions of uncertainty and instability of the market space, which can become the subject of further research.